Harvesting the power of serious game for IT education - Ariffin, M.M. (American Scientific Publishers, 2017)
This study aimed to investigate the effectiveness of game-based learning in supporting IT education. To attain this objective, the participants’ academic performance in terms of knowledge change was assessed. This study adopted the True-experimental research design involving 61 participants. Set of pre- and post-test was administered, where descriptive analysis and Independent Sample t-Test were performed to the collected data. The preand post-test questions were designed to assess the acquisition of knowledge on computer security principles and malicious threats to organization. The finding from this study suggested that participants who participated in game-based learning performed better. © 2017 American Scientific Publishers All rights reserved.